1990
DOI: 10.1039/ft9908603843
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum ultraviolet photoelectron spectroscopic study of the NH2O and HNO molecules

Abstract: UV photoelectron spectra have been recorded for the F + NH20H reaction at different reaction times. At short reaction times three bands associated with NH,O were observed, whereas at longer reaction times one band associated with NHO was seen.The NH20 bands were assigned with the aid of ab initio molecular orbital calculations which used an essentially planar equilibrium geometry for the neutral ground state. The HNO band showed resolved vibrational structure which was analysed in terms of excitation of the N-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0

Year Published

1993
1993
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…This work indicates that studies with TPE spectroscopy, supported by ab initio/Franck-Condon calculations, of other tri-and tetra-atomic reactive intermediates, in which vibrational structure in more than one vibrational mode in the first and higher PE bands is expected, is possible and this is planned for future work. Possible reactive intermediates that could be studied in this way include HO 2 , [43] HNO, [44] HCO, [45] CH 2 Cl and CHCl 2 . [46] In each case, the results should lead to a more reliable determination of the AIE, assignment of the observed vibrational structure and hence determination of vibrational frequencies in the ionic state.…”
mentioning
confidence: 99%
“…This work indicates that studies with TPE spectroscopy, supported by ab initio/Franck-Condon calculations, of other tri-and tetra-atomic reactive intermediates, in which vibrational structure in more than one vibrational mode in the first and higher PE bands is expected, is possible and this is planned for future work. Possible reactive intermediates that could be studied in this way include HO 2 , [43] HNO, [44] HCO, [45] CH 2 Cl and CHCl 2 . [46] In each case, the results should lead to a more reliable determination of the AIE, assignment of the observed vibrational structure and hence determination of vibrational frequencies in the ionic state.…”
mentioning
confidence: 99%
“…A more complex example of the isomers identification in this work is illustrated in Figure 5 for the ion at m/z 31. Although we could readily identify the methylamine (CH 5 N) and probably nitrosyl hydride (HNO) through comparison with the experimental PES by Bieri et al 43 and Baker et al 45 , the region above 10.8 eV is unexplained. Other candidate such CH 3 O radical [46][47] was also excluded by their cation's electronic footprint, and the fact that radicals are not expected in tholins.…”
Section: Molecular Identification Of the Lighter Ions With M/z < 69mentioning
confidence: 88%
“…H 2 NO was produced in the gas phase in 1984 by the reaction of fluorine atoms with NH 2 OH and identified by far infrared laser magnetic resonance. 11 Subsequent work using the same reaction yielded the photoelectron 12 and microwave spectra. 13 The latter study showed that H 2 NO has an essentially planar structure of C 2v symmetry and microwave spectroscopy 14 confirms that H 2 NS is also a planar molecule.…”
Section: Introductionmentioning
confidence: 98%